The Role of Library Management in Supporting Students’ Literacy and Critical Thinking - Putri, Idra; Putra, Hendra Eka; Juita, Novia; Ardi, Havid (MANDAILING GLOBAL EDUKASIA, 2025)
This study aimed to explore in depth the strategic role of school library management in supporting the development of literacy and critical thinking skills of students. This study was conducted through a comprehensive literature study, by analyzing various scientific sources such as academic journals, reference books, and relevant national education policy documents. The results of the study indicate that school libraries that are managed professionally and systematically are able to become effective learning resource centers, and make significant contributions to creating a conducive literary environment for active learning and the development of high-level thinking. Several managerial aspects that have been proven to have an important role include the management of relevant and actual collections, the use of information technology in library services, and increasing the capacity and competence of librarians as literacy facilitators. With proper management, the library not only functions as a place to store books, but also as a learning space that supports the achievement of 21st century education goals, especially in fostering students' information literacy and critical thinking skills. These findings emphasize the need to strengthen the function of libraries in the education ecosystem through supportive policies and managerial practices that are adaptive to the times.